2014
DOI: 10.2298/vsp1405503b
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cholesteatoma of the middle ear - uncommon clinical presentation

Abstract: The diagnosis of congenital cholesteatoma in children should always be considered, even if the clinical symptoms imitate other ear disorders, in our case otosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The recurrence rate of CMEC in children is 10.5% to 45%. [12,13] Most studies on CMEC are small scale [8,12,[14][15][16][17] ; therefore, it remains unclear whether otoendoscopy can reduce the CMEC recurrence rate. Advances in otoendoscopy have yielded otoendoscopes with a diameter of 2.7 and 1.9 mm, which can pass through the narrow ear canal to increase the surgical field of vision, improve the surgical field clarity, and observe tissue from multiple angles at close range.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate of CMEC in children is 10.5% to 45%. [12,13] Most studies on CMEC are small scale [8,12,[14][15][16][17] ; therefore, it remains unclear whether otoendoscopy can reduce the CMEC recurrence rate. Advances in otoendoscopy have yielded otoendoscopes with a diameter of 2.7 and 1.9 mm, which can pass through the narrow ear canal to increase the surgical field of vision, improve the surgical field clarity, and observe tissue from multiple angles at close range.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the recurrence rate of CMEC in children is 10.5%-45% [11,12]. At present most reports on CMEC are small-sample reports [7,11,[13][14][15][16], so there is no data to prove that otoendoscope can reduce the recurrence rate of CMEC. With the development of ear endoscopy, ear endoscopy with a diameter of 2.7 mm and 1.9 mm can pass through the narrow ear canal, increase the surgical eld of vision, improve the clarity of the surgical eld and observe tissue from multiple angles at close range [17].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesteatoma can be congenital or acquired ( Table 1 ), which may be distinguished based on the history, status of the TM and location of the lesion [ 8 10 ]. Congenital cholesteatoma (CC) develops from the embryonic epithelial rest which is most commonly located in the temporal bone but can be present elsewhere in the skull, including skin [ 8 , 11 ]. Unlike the acquired type, CC ( Figure 4 ) is not a sequelae of CSOM; nonetheless, it needs to be mentioned due to similar imaging findings [ 12 , 13 ].…”
Section: Imaging Modalities For the Evaluation Of Csom [ 5 mentioning
confidence: 99%